(untitled) (Bangladesh Journal of Medical Science, 2026)
Background The study involved 134 nurses working in anesthesia and intensive care units in the Rabat-Salé-Kénitra region, predominantly women (68%) and married (60%), with a mean age of 35.8 years and 18 years of professional experience. Psychometric evaluation confirmed good reliability of the burnout scale (α = 0.81) and the PSS-10 (α = 0.81). Result Results revealed substantial exposure to occupational stress and burnout, with high levels of emotional exhaustion (47.8%) and depersonalization (50.7%), while nearly half of participants reported high personal accomplishment. Although most nurses presented low to moderate levels of burnout (73.1%) and stress (78.4%), a significant proportion experienced high levels (p < 0.001). Attentional assessment showed that 59.7% of nurses were attentive and focused, whereas 40.3% exhibited attentional difficulties or impulsivity. Burnout (OR = 9.03) and perceived stress (OR = 3.39) were significantly associated with impaired attention. Multivariate analysis demonstrated strong explanatory power (R² = 0.727), identifying age and professional grade as significant predictors of adaptive attentional performance. Unexpectedly, global burnout was positively associated with adaptive attention, possibly reflecting compensatory mechanisms or methodological bias, while perceived stress was not significant. Conclusion Overall, the findings highlight the coexistence of moderate general profiles with a vulnerable high-risk subgroup, underlining the impact of burnout and stress on attentional functioning in high-demand clinical settings. Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 936-946